Electrolyte additive and preparation method thereof, non-aqueous electrolyte and alkali metal battery
By using oxathiheterocyclimine alkali metal salt compounds in alkali metal batteries to form a stable double-layer SEI film, the problem of dendrites is solved and the circulation performance and energy density of alkali metal batteries are improved.
Patent Information
- Application Number
- CN202311510421.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-09-02
- Estimated Expiration
- 2043-11-14
AI Technical Summary
Alkaline metal batteries are prone to dendrites during circulation, resulting in short circuits and reduced circulation efficiency. The recombination of the SEI film on the metal surface consumes electrolyte, affecting battery life.
Oxythiol heterocyclimine alkali metal salt compounds are used as electrolyte additives to form stable organic and inorganic bilayer SEI films, which jointly inhibit dendrites' growth and improve cycling performance.
Effectively inhibit dendrites' growth, improve the circulation performance and energy density of alkali metal batteries, and ensure the stability and reliability of the batteries.
Smart Images

Figure CN117551055B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte additive and a preparation method thereof, a non-aqueous electrolyte and an alkali metal battery. Background Art
[0002] At present, lithium-ion batteries have been widely used in technological products such as automobiles and mobile phones. Commercial lithium-ion batteries mainly use graphite as the negative electrode material, and its capacity is close to the theoretical value of graphite (372mAh / g). It is difficult to greatly increase the capacity of lithium-ion batteries by processing graphite. In order to obtain lithium-ion batteries with high capacity, metal materials such as silicon (4200mAh / g) and tin (990mAh / g) that have high storage capacity characteristics by alloying with lithium are used as negative electrode active materials. However, when metals such as silicon and tin are used as negative electrode active materials, their volume expands to about 4 times during the charging process of alloying with lithium, and shrinks again during the discharge process. Due to the repeated large volume changes of the electrode assembly during the charge / discharge process, the active material gradually pulverizes and falls off the electrode, so the capacity decreases rapidly, making it difficult to ensure stability and reliability, and thus leading to commercial failure. Compared with the above-mentioned negative electrode active materials, alkali metals such as lithium metal, sodium metal and potassium metal have higher specific capacity, especially metallic lithium, whose theoretical specific capacity is as high as 3860mAh / g and the electrode potential is as low as -3.04V (relative to H2 / H + ), so the development of alkali metal batteries with metallic lithium as the negative electrode has once again attracted the attention of scientific researchers. However, there are two main obstacles that limit the further development of alkali metal batteries: (1) Alkali metal batteries are prone to produce dendrites during the cycle, such as lithium dendrites. Lithium dendrites can easily pierce the battery's isolation membrane, causing the battery to be prone to short circuits; (2) Dendrites have a large surface area and high activity, and are prone to violent reactions with the electrolyte, resulting in continuous reorganization of the SEI film (interface film) on the metal surface, consuming electrolyte and active metals, and also resulting in reduced cycle efficiency and shortened battery cycle life. Therefore, how to effectively improve the surface properties of metal electrodes and inhibit the formation of metal dendrites is the key point that needs to be solved for the further development of alkali metal batteries.
[0003] Therefore, there is an urgent need for an electrolyte additive and a preparation method thereof, a non-aqueous electrolyte and an alkali metal battery to solve the above problems. Summary of the Invention
[0004] The object of the present invention is to provide an electrolyte additive and a preparation method thereof. The preparation method of the present invention can effectively synthesize the electrolyte additive, and the electrolyte additive of the present invention is applied to the non-aqueous electrolyte of alkali metal batteries to effectively inhibit the growth of metal dendrites, thereby improving the capacity and cycle performance of the alkali metal battery.
[0005] To achieve the above objectives, the present invention provides an electrolyte additive in a first aspect, having a structure as shown in Formula 1:
[0006]
[0007] Among them, A + For alkali metal ions.
[0008] Compared with the prior art, the electrolyte additive of the present invention is an alkali metal salt structure compound of an oxygen-sulfur heterocyclic imide. The O and N, N and S or O and S in the ring of the compound have a conjugated effect. The compound reacts at the electrode / electrolyte interface to form an organic SEI film with excellent stability. At the same time, the OSNA group is deposited at the electrode / electrolyte interface to form an organic SEI film rich in A3N, AN x O y ,AS x O y The double-layer SEI film formed by the organic SEI film and the inorganic SEI film has a synergistic effect, which can effectively inhibit the growth of metal dendrites and improve the cycle performance of alkali metal batteries, thus ensuring the high energy density advantage of alkali metal negative electrodes.
[0009] A second aspect of the present invention provides a method for preparing the above electrolyte additive, comprising the steps of:
[0010] S1 Chlorosulfonyl isocyanate reacts with ethylene glycol to form oxathioheterocyclic imine compounds;
[0011] S2: the oxygen-sulfur heterocyclic imine compound undergoes a substitution reaction with a metal source.
[0012] Compared with the prior art, the present invention uses chlorosulfonyl isocyanate and ethylene glycol as raw materials to react to prepare an intermediate product containing an oxythioheterocyclic imine compound, and then undergoes a substitution reaction with a metal source to prepare an oxythioheterocyclic imine alkali metal salt. This preparation method is simple and controllable.
[0013] Specifically, in S1, the reaction process of chlorosulfonyl isocyanate and ethylene glycol can be shown in Reaction Formula 1, and the resulting product is an oxythioheterocyclic imine compound, which is recorded as intermediate A:
[0014]
[0015] As a preferred technical solution, the metal source is selected from any one of lithium hydroxide, lithium carbonate, lithium methoxide, lithium ethoxide, sodium hydroxide, sodium carbonate, sodium methoxide and sodium ethoxide.
[0016] Specifically, in S2, the metal source is selected from lithium hydroxide, lithium carbonate, lithium methoxide, and lithium ethoxide. The reaction process of intermediate A and the metal source can be shown in Reaction Formula 2. The obtained product is the electrolyte additive, and the electrolyte additive is a lithium salt of oxathioheterocyclic imide, which is recorded as Compound 1.
[0017]
[0018] Specifically, in S2, the metal source is selected from sodium hydroxide, sodium carbonate, sodium methoxide, and sodium ethoxide. The reaction process of intermediate A and the metal source can be shown in Reaction Formula 3. The obtained product is the electrolyte additive, and the electrolyte additive is sodium salt of oxathioheterocyclic imine, which is recorded as Compound 2.
[0019]
[0020] As a preferred technical solution, the molar ratio of the chlorosulfonyl isocyanate to the ethylene glycol is 1:1-2, specifically but not limited to 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.5, 1:1.7, 1:1.8, 1:1.9, 1:2. The molar ratio of the oxysulfide heterocyclic imine compound to the metal source is 1:1-2, specifically but not limited to 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.5, 1:1.7, 1:1.8, 1:1.9, 1:2.
[0021] As a preferred technical solution, S1 comprises dropwise adding the chlorosulfonyl isocyanate to the ethylene glycol toluene solution at 0°C, heating the temperature to 120-140°C after the addition is complete and refluxing for 10-15 hours, followed by post-treatment to obtain the oxathioheterocyclic imine compound. For example, after the addition is complete, heating the temperature to 130°C and refluxing for 12 hours.
[0022] Specifically, the post-treatment includes washing, extraction, drying, concentration, and separation and purification. For example, the washing is performed using a saturated sodium chloride solution; the extraction is performed using dichloromethane; the drying is performed using anhydrous magnesium sulfate to dry the extracted and separated substances; the concentration is performed using a rotary evaporator under reduced pressure; and the separation and purification is performed using column chromatography.
[0023] As a preferred technical solution, S2 comprises reacting the oxathioheterocyclic imine compound and the metal source in anhydrous ethanol at 0°C for 10 to 14 hours, followed by post-treatment to obtain the oxathioheterocyclic imine alkali metal salt. For example, the reaction time is 12 hours.
[0024] Specifically, the post-treatment includes concentration and recrystallization. For example, the concentration is to concentrate the reaction solution under reduced pressure using a rotary evaporator; and the recrystallization is to recrystallize the concentrated solution using dichloromethane.
[0025] The third aspect of the present invention provides a non-aqueous electrolyte, comprising a non-aqueous solvent, an electrolyte salt, and the above-mentioned electrolyte additive or the electrolyte additive prepared by the above-mentioned preparation method, wherein the mass percentage of the electrolyte additive in the non-aqueous electrolyte is 0.01% to 2.00%, specifically but not limited to 0.01%, 0.05%, 0.10%, 0.50%, 1.00%, 1.20%, 1.40%, 1.60%, 1.80%, and 2.00%.
[0026] As a preferred technical solution, the electrolyte salt is any one of a lithium salt and a sodium salt, and the mass percentage of the electrolyte salt in the non-aqueous electrolyte is 8% to 14%, specifically but not limited to 8%, 9%, 10%, 11%, 12%, 12.5%, 13%, 13.5%, and 14%.
[0027] Specifically, the electrolyte salt corresponds to the electrolyte additive. For example, if the electrolyte salt is a lithium salt, the electrolyte additive is compound 1; if the electrolyte salt is a sodium salt, the electrolyte additive is compound 2.
[0028] As a preferred technical solution, the lithium salt is specifically but not limited to one or more of lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroantimonate (LiSbF6), lithium difluorophosphate (LiPF2O2), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium 4,5-dicyano-2-trifluoromethylimidazolium (LiDTI) and lithium bis(fluorosulfonyl)imide (LiFSI).
[0029] As a preferred technical solution, the sodium salt is specifically but not limited to one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium hexafluoroantimonate (NaSbF6), sodium difluorophosphate (NaPF2O2), sodium 4,5-dicyano-2-trifluoromethylimidazolium (NaDTI), sodium bis(oxalyl)borate (NaBOB), sodium difluorooxalatoborate (NaDFOB) and sodium bis(fluorosulfonyl)imide (NaFSI).
[0030] As a preferred technical solution, the non-aqueous electrolyte also includes an additive, including at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), vinyl sulfinate (ES), 1,3-propane sultone (1,3-PS), and diethyl sulfonate (DTD). Vinyl ethylene carbonate (VEC) is preferred. VEC has a very low LUMO energy level (-0.82 eV) and preferentially decomposes on the surface of the alkali metal anode to form a polycarbonate-rich SEI film. Polycarbonate's adhesiveness and flexibility help the SEI film adapt to the stress caused by the volume change of the alkali metal anode, thereby improving the stability of the SEI film.
[0031] As a preferred technical solution, the mass percentage of the auxiliary agent in the non-aqueous electrolyte is 0.1% to 5%, specifically but not limited to 0.1%, 0.2%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, and 5.0%.
[0032] As a preferred technical solution, the non-aqueous solvent is at least one of a chain carbonate, a cyclic carbonate, a carboxylate, and a lactone. Preferably, the non-aqueous organic solvent is a mixture of the chain carbonate and the cyclic carbonate.
[0033] Specifically, the linear carbonate may be at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), propyl methyl carbonate (PMC), and ethyl propyl carbonate (PEC). As an example, the linear carbonate may be, but is not limited to, any one of ethylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), or any combination thereof, to achieve relatively stable cycling performance.
[0034] Specifically, the cyclic carbonate can be at least one of ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), butylene carbonate, and pentylene carbonate, preferably fluoroethylene carbonate (FEC). This is beneficial for improving the cycle performance of the battery. This is likely due to the introduction of fluoroethylene carbonate (FEC) molecules, which have a stronger affinity for metal ions, into the metal ion solvation shell, lowering the metal ion desolvation energy barrier and thus reducing the polarization of the metal ion deposition and desolvation process. Simultaneously, the FEC molecules coordinated with the metal ions preferentially decompose on the metal surface to form a fluoride-rich SEI film, which can reduce the metal ion diffusion energy barrier in the SEI film and induce uniform metal deposition.
[0035] Specifically, the carboxylate may be at least one of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate.
[0036] Specifically, the lactone may be at least one of γ-butyrolactone, γ-valerolactone, γ-caprolactone, o-valerolactone, and e-caprolactone.
[0037] The fourth aspect of the present invention provides an alkali metal battery, including a positive electrode material and a negative electrode material, and further including the above-mentioned non-aqueous electrolyte.
[0038] As a preferred technical solution, the negative electrode material is a lithium alloy or lithium metal, and the positive electrode material is a lithium cobalt oxide material, a lithium iron phosphate material, a nickel cobalt manganese oxide, or a nickel cobalt aluminum oxide. The lithium cobalt oxide material is lithium cobalt oxide or lithium cobalt oxide modified by doping and coating, the lithium iron phosphate material is lithium iron phosphate or lithium iron phosphate modified by doping and coating, and the chemical formula of the nickel cobalt manganese oxide is LiNi x Co y M (1-x-y-z) O2, and the chemical formula of the nickel cobalt aluminum oxide is LiNi x Co y Al z N (1-x-y-z) O2, where M is at least one of Mg, Cu, Zn, A1, Sn, B, Ga, Cr, Sr, V, and Ti, N is at least one of Mn, Mg, Cu, Zn, Sn, B, Ga, Cr, Sr, V, and Ti, 0 ≤ 1, 0 < y < 1, 0 < z < 1, and x + y + z ≤ 1. When the negative electrode material is sodium metal or a sodium alloy, the positive electrode material is a composite metal oxide similar to the positive electrode of a lithium metal battery. Of course, the positive electrode material may also be other materials that can undergo ion deintercalation with sodium ions. Detailed implementation manners
[0039] To better illustrate the purpose, technical solution, and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following embodiments are further explanatory descriptions of the present invention and should not be construed as limitations on the present invention.
[0040] For those conditions not specified in the present invention, they can be carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments whose manufacturers are not specified, they are all conventional products that can be obtained through commercial channels.
[0041] Part I
[0042] This part provides an electrolyte additive having the structure shown in Formula I:
[0043]
[0044]
[0045] Where A + is Li+ Or Na + .
[0046] The preparation method of the electrolyte additive in this section comprises the following steps:
[0047] S1: 20 g of ethylene glycol was added to a dry 500 mL three-necked flask, 150 g of toluene was added as a solvent, and the flask was placed in a 0°C water bath. 46 g of chlorosulfonyl isocyanate was added dropwise thereto. After the addition was complete, the temperature was raised to 130°C and the reaction system was refluxed for 12 hours. After the reaction was completed, the flask was washed with a saturated sodium chloride solution, extracted with dichloromethane, separated, dried over anhydrous magnesium sulfate, concentrated, and separated and purified by column chromatography to obtain 10 g of an oxathiamine compound.
[0048] S2: Add 10g of the intermediate product and 1.4g of anhydrous lithium hydroxide (or 2.4g of anhydrous sodium hydroxide) to a dry 500ml three-necked flask, add 100g of anhydrous ethanol as a solvent, and allow the reaction system to react in a 0°C water bath for 12h. After the reaction is completed, the reaction solution is concentrated, and dichloromethane, a recrystallization solvent, is added to the reaction solution. The reaction mixture is filtered to obtain the target product. + For Li + (ie, the metal source is anhydrous lithium hydroxide) to obtain 8.1 g of product, which is compound 1; A + for Na + (ie the metal source is anhydrous sodium hydroxide) 8.6 g of product was obtained, which is compound 2. Compound 1 and compound 2 are both white solids, and the results of nuclear magnetic resonance hydrogen spectrum are 1 H NMR (60 MHz, d-DMSO) δ 4.38 (t, J = 9.6 Hz, 2H), 3.81 (t, J = 9.5 Hz, 2H). The structures of Compound 1 and Compound 2 are shown below:
[0049]
[0050] Part 2
[0051] This section describes the use of the electrolyte additive compound 1 of Example 1 in a non-aqueous electrolyte for lithium metal batteries. The following details the preparation of the electrolyte, positive electrode, separator, and negative electrode, preparation of the lithium metal battery, and the test conditions for cycling performance for Group 1 of this section.
[0052] (1) Preparation of electrolyte
[0053] Under an argon atmosphere and in a vacuum glove box with a moisture content of <1 ppm, ethyl methyl carbonate (EMC) and fluoroethylene carbonate (FEC) were mixed in a weight ratio of EMC:FEC = 2:3. Then, 0.5 g of compound 1 was added, dissolved, and stirred thoroughly. After that, 12.5 g of lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte.
[0054] (2) Preparation of positive electrode
[0055] Lithium cobalt oxide LiCoO2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 95:1:4 to prepare a lithium metal battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, dried and rolled to obtain a positive electrode sheet.
[0056] (3) Preparation of diaphragm
[0057] Polyethylene (PE) with a thickness of about 15 μm was used as the separator.
[0058] (4) Preparation of negative electrode
[0059] Lithium metal is composited onto a 10μm-thick copper foil current collector using a physical roller pressing method. The roller pressure is adjusted to ensure lithium coverage on both sides of the copper current collector, with a thickness of approximately 35μm. This creates a lithium-copper composite tape anode. After being cut and slit, the strips are stored in a dry argon atmosphere glove box until ready for use.
[0060] (5) Preparation of lithium metal batteries
[0061] The positive electrode sheet, separator, and lithium-copper composite tape negative electrode sheet are stacked in order and then stacked as needed. After welding, the tabs are placed in the aluminum-plastic film of the battery packaging. The prepared electrolyte is injected into the dried bare battery cell. The process is vacuum packaging, static, formation (0.05C constant current charging to 3.6V, then 0.1C constant current charging to 3.9V), shaping, and capacity testing to finally obtain a 1Ah soft-pack lithium metal battery.
[0062] (6) Cycle performance
[0063] The lithium metal battery was charged and discharged once at 0.5C / 0.5C at 25°C (the battery discharge capacity is C0) with an upper limit voltage of 4.55V. Then, it was charged and discharged at 0.5C / 0.5C for 300 cycles at room temperature (the battery discharge capacity is C1). The capacity retention rate was calculated according to the following formula:
[0064] Capacity retention rate = (C1 / C0) × 100%
[0065] The electrolyte formulations and cycle performance test results of Groups 2 to 9 are shown in Table 1. The steps for preparing the electrolyte, preparing the battery, and the cycle performance test methods are the same as those of Group 1.
[0066] Table 1
[0067]
[0068] As can be seen from Table 1, the lithium metal battery containing the electrolyte additive compound 1 of the present invention has better cycle performance.
[0069] Part 3
[0070] This section describes the use of the electrolyte additive compound 2 prepared in Example 1 in a non-aqueous electrolyte for a sodium metal battery. The following details the preparation of the electrolyte, positive electrode, separator, and negative electrode, the preparation of the sodium metal battery, and the cycling performance testing conditions for Group 1.
[0071] (1) Preparation of electrolyte
[0072] Under an argon atmosphere and in a vacuum glove box with a moisture content of <1 ppm, ethyl methyl carbonate (EMC) and fluoroethylene carbonate (FEC) were mixed in a weight ratio of EMC:FEC = 2:3. Then, 0.5 g of compound 2 was added, dissolved, and stirred thoroughly. After that, 12.5 g of sodium hexafluorophosphate (NaPF6) was added and mixed evenly to obtain an electrolyte.
[0073] (2) Preparation of positive electrode
[0074] Sodium cobaltate NaCoO2, binder PVDF and conductive agent SuperP are evenly mixed in a mass ratio of 95:1:4 to prepare a sodium metal battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, dried and rolled to obtain a positive electrode sheet.
[0075] (3) Preparation of diaphragm
[0076] Polyethylene (PE) with a thickness of about 15 μm was used as the separator.
[0077] (4) Preparation of negative electrode
[0078] Sodium metal is composited onto a 10μm-thick copper foil current collector using a physical roller press. The roller pressure is adjusted to coat both sides of the copper current collector with sodium, with a thickness of approximately 35μm. This creates a sodium-copper composite tape anode. After cutting and slitting, the material is stored in a dry argon-filled glove box until ready for use.
[0079] (5) Preparation of sodium metal batteries
[0080] The positive electrode sheet, separator, and sodium-copper composite tape negative electrode sheet are stacked in order and then stacked as needed. After welding, the tabs are placed in the aluminum-plastic film of the battery packaging. The prepared electrolyte is injected into the dried bare cell. The cells are then vacuum packaged, allowed to stand, formed (charged at a constant current of 0.05C to 3.6V, then at a constant current of 0.1C to 3.9V), shaped, and tested for capacity. Finally, a 1Ah soft-pack sodium metal battery is obtained.
[0081] (6) Cycle performance
[0082] The sodium metal battery was charged and discharged once at 0.5C / 0.5C at 25°C (the battery discharge capacity is C0) with an upper voltage of 4.55V. Then, it was charged and discharged at 0.5C / 0.5C for 300 cycles at room temperature (the battery discharge capacity is C1). The capacity retention rate was calculated according to the following formula:
[0083] Capacity retention rate = (C1 / C0) × 100%
[0084] The electrolyte formulations and cycle performance test results of Groups 2 to 9 are shown in Table 2. The steps for preparing the electrolyte, preparing the battery, and the cycle performance test methods are the same as those of Group 1.
[0085] Table 2
[0086]
[0087]
[0088] As shown in Table 2, the sodium metal battery containing the electrolyte additive compound 2 of the present invention has better cycle performance.
[0089] In summary, the addition of the electrolyte prepared by the present invention to an alkali metal battery can effectively improve the cycle performance of the alkali metal. This may be because the electrolyte additive of the present invention is an alkali metal salt structure compound of an oxygen-sulfur heterocyclic imide. The O and N, N and S, or O and S in the ring of the compound have a conjugated effect, which reacts at the electrode / electrolyte interface to form an organic SEI film with excellent stability. At the same time, the OSNA group (A is an alkali metal) is deposited at the electrode / electrolyte interface to form an organic SEI film rich in A3N, AN x O y ,AS x O y The double-layer SEI film formed by the organic SEI film and the inorganic SEI film has a synergistic effect, which can effectively inhibit the growth of metal dendrites and improve the cycle performance of alkali metal batteries. This shows that the electrolyte additive of the present invention has a good application prospect in alkali metal ion batteries.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. An electrolyte additive, characterized in that It has the structure shown in Formula 1: Among them, A + For alkali metal ions.
2. A method for preparing the electrolyte additive according to claim 1, characterized in that: Including steps: S1 Chlorosulfonyl isocyanate reacts with ethylene glycol to form oxathioheterocyclic imine compounds; S2: the oxygen-sulfur heterocyclic imine compound undergoes a substitution reaction with a metal source.
3. The method for preparing the electrolyte additive according to claim 2, characterized in that: The metal source is selected from any one of lithium hydroxide, lithium carbonate, lithium methoxide, lithium ethoxide, sodium hydroxide, sodium carbonate, sodium methoxide and sodium ethoxide.
4. The method for preparing the electrolyte additive according to claim 2, wherein: The molar ratio of the chlorosulfonyl isocyanate to the ethylene glycol is 1:1-2, and the molar ratio of the oxythioheterocyclic imine compound to the metal source is 1:1-2.
5. The method for preparing the electrolyte additive according to claim 2, characterized in that: The S1 comprises dropwise adding the chlorosulfonyl isocyanate to the toluene solution of ethylene glycol at 0° C., heating to 120-140° C. after the dropwise addition is complete, and then refluxing for 10-15 hours, followed by post-treatment to obtain the oxythioheterocyclic imide compound.
6. The method for preparing the electrolyte additive according to claim 2, characterized in that: The S2 comprises the oxythioheterocyclic imine compound and the metal source, reacting in anhydrous ethanol at 0° C. for 10 to 14 hours, and then post-processing to obtain the electrolyte additive.
7. A non-aqueous electrolyte comprising a non-aqueous solvent and an electrolyte salt, characterized in that: It also includes the electrolyte additive according to claim 1 or the electrolyte additive prepared by the preparation method according to any one of claims 2 to 6, and the mass percentage of the electrolyte additive in the non-aqueous electrolyte is 0.01% to 2.00%.
8. The non-aqueous electrolyte according to claim 7, characterized in that The electrolyte salt is any one of a lithium salt and a sodium salt, and the mass percentage of the electrolyte salt in the non-aqueous electrolyte is 8% to 14%.
9. The non-aqueous electrolyte according to claim 7, characterized in that The invention further comprises an auxiliary agent, wherein the auxiliary agent comprises at least one of vinylene carbonate, vinyl ethylene carbonate, vinyl sulfinate, 1,3-propane sultone and vinyl sulfonate.
10. An alkali metal battery comprising a positive electrode material and a negative electrode material, characterized in that: It also includes the non-aqueous electrolyte according to any one of claims 7 to 9.
Citation Information
Patent Citations
Acesulfame lithium and preparation method thereof, and application in non-aqueous electrolytic solution
CN111333595A
Acesulfamic acid salt, preparation method thereof and application of acesulfamic acid salt in non-aqueous electrolyte
CN114436992A